2012
DOI: 10.1021/ie3015582
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Characteristic Analysis, and Optimization of Ideal Internal Thermally Coupled Air Separation Columns

Abstract: Cryogenic air separation is currently the most widely used but energy-intensive technology for producing large quantities of oxygen and nitrogen, where cryogenic distillation consumes about 75% of the whole air separation field; however, its thermodynamic efficiency is very low. A novel structure of a full tower ideal internal thermally coupled air separation column (ITCASC) is therefore first proposed in this paper. A rigorous mathematic model and parameter analysis are then presented. Research results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…The pressure of the HPC decreased to 0.395 MPa. Chang et al [33] and Chang and Liu [34] investigated the modeling, characteristic analysis and optimization of a fully coupled heat-integrated air separation column (HIASC), where the ideal pressure dropped to 0.39 MPa. Fig.…”
Section: Research Articlementioning
confidence: 99%
See 3 more Smart Citations
“…The pressure of the HPC decreased to 0.395 MPa. Chang et al [33] and Chang and Liu [34] investigated the modeling, characteristic analysis and optimization of a fully coupled heat-integrated air separation column (HIASC), where the ideal pressure dropped to 0.39 MPa. Fig.…”
Section: Research Articlementioning
confidence: 99%
“…Fig. 2 shows a schematic diagram of the fully coupled HIASC, which has been described in more detail elsewhere [33].…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…In order to provide the necessary thermal driving force for the heat transfer, the rectifying section is operated at a higher pressure than the stripping section. [5][6][7][8][9][10][11][12] Recently, a work by Cabrera-Ruiz et al 13 has shown that when one includes the compressing energy the savings are significantly affected, and in some cases hybrid structures which combine HIDiC (heat-integrated distillation column) and conventional columns have been proved to have higher economic potential than that totally using HIDiC in the separation of ternary mixtures, which reveals that the use of HIDiC should be carefully investigated for certain mixtures before real applications.…”
Section: Introductionmentioning
confidence: 99%